Enhancing development trajectories of synthetic environments. Issue 1 (2018) - Damgrave, Roy; Lutters, Eric
Abstract: This research presents a framework that supports all stakeholders in the development of a Synthetic Environment. Guidance and support are provided throughout the entire process of development. Multiple disciplines are involved in this process, and the communication and collaboration between them is facilitated in such a way that mutual understanding is enhanced. Moreover, the rationale of decisions made throughout the development can be documented and accessed in such a way that all stakeholders can review and comprehend these decisions in relation to the prior and underlying decision-making processes.